The Language System in Cognitive Science: Framing and Computation From the Human Mind to the Computational Mind - Kaddouri, Abdelmajid; Boutayeb, Abdelhaq (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The cognitive revolution brought by modern linguistic theories has compelled researchers to explore increasingly complex issues concerning the mental processes involved in language, often situated at the intersection of multiple disciplines. In the current era, where technological sciences dominate and serve as a driving force for the advancement of all human sciences, a new interdisciplinary field has emerged—one that bridges linguistics and computer science. This study addresses the central problem of how the language system in the human mind can be logically and formally represented for computational purposes. The objective of this paper is to examine the modular and computational structures of language from the perspective of cognitive sciences, focusing on the phonological lexicon, morphological lexicon, and lexical semantics. The study employs a qualitative-descriptive method, with a theoretical analysis approach that synthesizes concepts from linguistics, cognitive psychology, and computer science. The findings demonstrate that the construction of a computational mental lexicon enables the standardization of linguistic data in computer memory and facilitates the automation of language processing across linguistic levels. The main contribution of this research lies in offering a conceptual framework for building natural language processing systems grounded in cognitive and linguistic principles. Such systems not only simulate how humans perceive, store, and produce language but also bring us closer to modeling a computational theory of mind. This reinforces the strategic role of linguistics in the digital age and its vital relevance in advancing intelligent language technologies.